Continuous Requirement for Host P10 Protein During Bacteriophage T4 Infection - Cafferata, Robert L. (1970)
The Escherichia coli 30S ribosomal protein P10, the product of the str gene, known to be involved only in the initiation of protein syntehsis, is required for all bacteriophage T4 protein synthesis.